CHANGES OF RATS BODY WEIGHT DURING LONG-TERM MONOSODIUM GLUTAMATE FEEDING - Falalyeyeva, T.M. (World of Medicine and Biology, 2012)
The influence of prolonged administration of monosodium glutamate (MSG) on body weight in rats was studied. Found that 10 -, 20 -, 30-days feeding by MSG in doses 15 to 30 mg/kg (equivalent to 1 and 2 g/person) leads to increased of body weight. It is concluded that prolonged, excessive and systemic use of MSG causes obesity. Secondly, the maximum dose of MSG should be reconsidered taking into account its influence on body weight.
Keywords: Monosodium glutamate; obesity